Evaluation of the theory of mind in autism spectrum disorders with the Strange Stories test - Renata de Lima Velloso; Cintia Perez Duarte; Jose Salomao Schwartzman (Arquivos de Neuro-Psiquiatria)
Objective To evaluate the theory of mind in autism spectrum disorders (ASD) and control individuals by applying the Strange Stories test that was translated and adapted to the Portuguese language. Method Twenty-eight children with ASD and 56 controls who were all male and aged between 6 and 12 years participated in the study. Results There were significant differences between the median scores of the groups for each of the 12 stories of the test and for the sum total of all the median scores. The median scores for all stories were significantly greater in the control group than those in the experimental group (children with ASD). In addition, the protocol had excellent internal consistency. Conclusion The theory of mind skills assessed with the Strange Stories test indicated alterations in children with ASD compared with children in the control group.